The Latest in Animal Models of Pulmonary Hypertension and Right Ventricular Failure. Issue 9 (29th April 2022) - Boucherat, Olivier; Agrawal, Vineet; Lawrie, Allan; Bonnet, Sebastien
Abstract : Pulmonary hypertension (PH) describes heterogeneous population of patients with a mean pulmonary arterial pressure >20 mm Hg. Rarely, PH presents as a primary disorder but is more commonly part of a complex phenotype associated with comorbidities. Regardless of the cause, PH reduces life expectancy and impacts quality of life. The current clinical classification divides PH into 1 of 5 diagnostic groups to assign treatment. There are currently no pharmacological cures for any form of PH. Animal models are essential to help decipher the molecular mechanisms underlying the disease, to assign genotype-phenotype relationships to help identify new therapeutic targets, and for clinical translation to assess the mechanism of action and putative efficacy of new therapies. However, limitations inherent of all animal models of disease limit the ability of any single model to fully recapitulate complex human disease. Within the PH community, we are often critical of animal models due to the perceived low success upon clinical translation of new drugs. In this review, we describe the characteristics, advantages, and disadvantages of existing animal models developed to gain insight into the molecular and pathological mechanisms and test new therapeutics, focusing on adult forms of PH from groups 1 to 3. We also discuss areas of improvement for animal models with approaches combining several hits to better reflect the clinical situation and elevate their translational value.